Respuesta :

Answer: -3

Step-by-step explanation:

g(0) means .... what is the y-value of g when x = 0

When x = 0, g(x) = -1

f(g(0)) → f(-1) ... what is the y-value of f when x = -1

When x = -1, f(x) = -3

Using the table given alongside, and from composite function property, f(g(0)) is -3.

What are composite functions ?

A composite function of two functions combines the given two functions in a specific order. For any given two functions f(x) and g(x), there can be two composite functions: f(g(x)) which is substituting g(x) into f(x) and g(f(x)) which is substituting f(x) into g(x).

How to find the given composite functions ?

We have to find the value of composite function f(g(0)).

Now from the table, g(0) = -1 as when the value of x = 0, then the value of g(x) = -1.

Now, we have to find f(-1),

Thus, f(-1) = -3 as when the value of x = -1, then the value of f(x) = -3.

∴  From composite function property f(g(0)) = -3

Therefore, by using the table given alongside, and from composite function property, f(g(0)) is -3.

To learn more about composite function, refer -

https://brainly.com/question/17256873

#SPJ2